A clinical prognostic scoring system for Guillain-Barré syndrome - van Koningsveld, Rinske; Steyerberg, Ewout W; Hughes, Richard AC; Swan, Anthony V; van Doorn, Pieter A; Jacobs, Bart C (Lancet neurology, 2007)
Guillain-Barré syndrome (GBS) is an acute post-infectious immune-mediated peripheral neuropathy with a highly variable clinical course and outcome. We aimed to develop and validate a scoring system based on clinical characteristics in the acute phase of GBS to predict outcome at 6 months. We studied patients with GBS who were unable to walk independently. A derivation set included 388 patients from two randomised controlled trials and one pilot study. Potential predictors were assessed for their association with the inability to walk independently at 6 months. A simple clinical scoring system was developed on the basis of regression coefficients of predictors in a multivariable logistic regression model. Model performance was quantified with respect to discrimination (area under receiver operating characteristics curve, AUC) and calibration (graphically). We validated our scoring system in a set of 374 patients from another randomised trial. We included three variables that were predictive of poor outcome at 6 months in our model: age, preceding diarrhoea, and GBS disability score at 2 weeks after entry. Scores ranged from 1 to 7, with three categories for age, two for diarrhoea, and five for GBS disability score at 2 weeks. Predictions corresponding to these prognostic scores ranged from 1% to 83% for the inability to walk independently at 6 months. Predictions agreed well with observed outcome frequencies (adequate calibration) and showed a very good discriminative ability (AUC 0·85) in both data sets. A simple scoring system for patients with GBS, based on three clinical characteristics, accurately predicts outcome at 6 months. The system could be used to counsel individual patients and identify high-risk groups to guide future trials.